Efforts to Improve Student Learning Outcomes through the True or False Strategy Using Index Card Media - Pristianti, Agustina Dwi; Hartati, Zainap; Syabrina, Muhammad (LP3M Universitas Islam Zainul Hasan Genggong, 2025)
This study uses the Classroom Action Research (CAR) method to improve student learning outcomes in Fiqh learning. The subjects of the study were 25 students of class V MI Al-Jihad, Palangka Raya City. The object of the study was the application of the True Or False strategy using index card media. This study was conducted from March 2025 to May 2025. The location of this research was at MI Al Jihad, Palangka Raya City. Based on the results of class V Fiqh learning, it was found that the problem of learning achievement in the Fiqh subject was still low, this was proven by the percentage of daily test results, namely 50% of 25 students had not reached the KKM. The true or false learning strategy using index cards has been proven to improve student learning outcomes because the final result of the strategy application in cycle 1 was that 52% of 25 students got scores above the KKM and the percentage of KKM achievement in cycle 2 was 88%. The result of the N-Gain calculation is 3, which means that the increase is categorized as high and significant.